Elementary Teachers’ Perceptions, Readiness, and Challenges in Using Interactive Deep Learning–STEM-PBL Modules - Winda Oktaviana; Abdurrahman Abdurrahman; Dwi Yulianti (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study examines elementary school teachers’ perceptions, readiness, and challenges in using and developing interactive teaching modules based on pedagogical deep learning integrated with Problem-Based Learning (STEM-PBL) to support scientific literacy and communication. This study adopted an exploratory cross-sectional design, collecting data from 100 elementary teachers in Lampung Province, Indonesia, through online questionnaires, document analysis, and in-depth interviews. The findings indicate that while most teachers demonstrate positive perceptions toward interactive Deep Learning–STEM-PBL modules, their readiness to implement such approaches varies and is constrained by limited pedagogical competence, instructional design skills, and professional development opportunities. Document analysis further reveals a clear perception–practice gap, as most teaching modules do not yet explicitly integrate deep learning principles and STEM-PBL stages. Key challenges include insufficient training, time constraints, limited instructional references, and inadequate institutional support. Based on these findings, this study proposes a Teacher Readiness Framework for Deep Learning–STEM-PBL, which conceptualizes readiness as the interaction between teachers’ perceptions, multidimensional pedagogical capacities, and structural–institutional conditions that influence instructional practice outcomes.